MEMAHAMI KONSEP DASAR PENELITIAN KUALITATIF - Akin, M. Aris; Rahman, Ulfiani; Ondeng, Syarifuddin (Pusat Pengembangan Pendidikan dan Penelitian Indonesia, 2026)
ABSTRACT Qualitative research makes an important contribution to educational studies as it enables researchers to gain an in-depth understanding of learning processes, experiential meanings, and social contexts. Nevertheless, limitations in conceptual understanding among educational researchers persist, particularly with regard to the characteristics, procedures, and principles of trustworthiness in qualitative research. This article aims to examine and systematically synthesize the fundamental concepts of qualitative research in the field of education. The study employs a library-based research method with a descriptive-analytical approach, involving stages of literature searching, selection, classification, and critical analysis of relevant scholarly sources, including methodological books and reputable journal articles. The findings indicate that qualitative research is characterized by a naturalistic approach, a focus on meaning, inductive analysis, and the positioning of the researcher as a key instrument in data collection and analysis. Furthermore, the quality and trustworthiness of qualitative research data are ensured through the application of credibility, transferability, dependability, and confirmability criteria. This study concludes that a comprehensive understanding of the fundamental concepts and principles of qualitative research is a crucial prerequisite for producing systematic, academically accountable, and meaningful educational research in both academic and practical contexts. ABSTRAK Penelitian kualitatif memiliki kontribusi penting dalam kajian pendidikan karena memungkinkan peneliti memahami proses pembelajaran, makna pengalaman, serta konteks sosial secara mendalam. Meskipun demikian, masih dijumpai keterbatasan pemahaman konseptual di kalangan peneliti pendidikan terkait karakteristik, prosedur, dan prinsip keabsahan penelitian kualitatif. Artikel ini bertujuan untuk mengkaji dan mensintesis konsep dasar penelitian kualitatif dalam bidang pendidikan secara sistematis. Penelitian ini menggunakan metode studi pustaka dengan pendekatan deskriptif-analitis melalui tahapan penelusuran, seleksi, klasifikasi, dan analisis kritis terhadap literatur ilmiah yang relevan, meliputi buku metodologi dan artikel jurnal bereputasi. Hasil kajian menunjukkan bahwa penelitian kualitatif memiliki ciri utama berupa pendekatan naturalistik, orientasi pada makna, analisis induktif, serta penempatan peneliti sebagai instrumen kunci dalam pengumpulan dan analisis data. Selain itu, mutu dan keabsahan data dalam penelitian kualitatif ditentukan melalui penerapan kriteria kredibilitas, transferabilitas, dependabilitas, dan konfirmabilitas. Kajian ini menyimpulkan bahwa pemahaman yang komprehensif terhadap konsep dan prinsip dasar penelitian kualitatif menjadi prasyarat penting untuk menghasilkan penelitian pendidikan yang sistematis, dapat dipertanggungjawabkan secara ilmiah, dan bermakna dalam konteks akademik maupun praktis.